A Case of Severe Cardiac Sarcoidosis with Minimal Pulmonary Involvement: A Case Report with Literature Review. Issue 2 (June 2018) - Fowler, Mark R.; Mambo, Nobby C.
Sarcoidosis is a granulomatous disease of unknown etiology. Although sarcoidosis is a systemic disease, there appears to be a predilection for involvement of certain organs. The pulmonary system is the most commonly affected system among all racial groups. Cardiac and respiratory complications are the leading causes of death due to sarcoidosis and in certain patient populations about half of these deaths are attributed to cardiac sarcoidosis. There are few autopsy case reports of cardiac sarcoidosis with minimal respiratory involvement making this case report relevant to the importance of the recognition and awareness of this entity. Acad Forensic Pathol. 2018 8(2): 407-415